A Multimodal Study of Childhood Trauma and Distress Tolerance in Young Adulthood. Issue 7 (9th August 2018) - Berenz, Erin C.; Vujanovic, Anka; Rappaport, Lance M.; Kevorkian, Salpi; Gonzalez, Rose Emily; Chowdhury, Nadia; Dutcher, Christina; Dick, Danielle M.; Kendler, Kenneth S.; Amstadter, Ananda
ABSTRACT: Individuals with a history of childhood trauma experience deficits in emotion regulation. However, few studies have investigated childhood trauma and both perceived (i.e., self-report) and behavioral measures of distress tolerance. The current study evaluated associations between childhood trauma (i.e., physical abuse, sexual abuse, and witnessing family violence) and measures of perceived (Distress Tolerance Scale) and behavioral distress tolerance (i.e., Paced Auditory Serial Addition Test, breath-holding). Participants were 320 undergraduate students with a history of interpersonal trauma (e.g., sexual/physical assault). Structural equation modeling was used to evaluate associations between frequency of childhood trauma type and distress tolerance. Greater childhood physical abuse was associated with higher perceived distress tolerance. Greater levels of witnessing family violence were associated with lower behavioral distress tolerance on the breath-holding task. No significant effects were found for Paced Auditory Serial Addition Test performance. Associations between childhood trauma and emotion regulation likely are complex and warrant further study.